Leadership As an Effective Means in Management Activities - Murotmusaev Komiljon Buribaevich; Rizaeva Shalola; Sheryigit Ergashevich Yuldashev (Genius Journals, 2022)
The article deals with the issues of effective leadership in different organizations. The authors describe and analyze the elements of situational leadership and consider the relationship between personal characteristics of a person and his leadership abilities. Illustrative examples of leadership qualities in different historical persons are given
Keywords: Leadership; effective leadership; situational leadership; management